Profundidad de siembra de semillas de soya (Glycine max L.) y su efecto sobre el proceso de germinación y desarrollo - Castro Mora, José Miguel (2017)
VIII. SUMMARY The present research work was carried out in the Technical Laboratories of the Experimental Farm "San Pablo", of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located in the 7 ½ km of the Babahoyo - Montalvo road. The zone presents 8 msnm of height, with geographical coordinates 790 32` of longitude west and 10 49` of south latitude. The objectives were to: Identify adequate seed depth and evaluate the effect of germination and development of soybean seedlings. As seed material, soybean seed INIAP-308 was used. The treatments were constituted by the different seeding depths of the seed, at 3, 6, 9, 12, 15 and 18 cm. The experimental design was completely randomized, with six treatments and three replicates. The comparison of the means was done with the Tukey test at 95% probability. Cultivation work was carried out for the next test, such as drawer construction, substrate placement, seeding, weed control and irrigation. The evaluated data were taken in ten plants at random in each of the experimental units and were percentage of germination and physiological state of the plants that includes plant height and leaf number. From the results obtained in the present investigation it was determined that the depth of sowing influenced in the effect on the process of germination and development of soybean seeds; The highest germination percentage from 3 to 30 days after sowing was reported with depth of 3 cm; The plant height obtained results from 6 days after sowing, standing out the depth of sowing of 3 cm and 3 and 6 days was not observed the presence of leaves, however from 9 days the depth of 3 cm reached 2 leaves, increasing progressively until the 30 days that 14 leaves were observed.